2023
DOI: 10.1248/bpb.b23-00157
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for Infusion-Related Reactions Following Rituximab Administration in Patients with Desensitization before Renal Transplantation

Hironobu Nishiura,
Masaya Takahashi,
Tomoaki Iwai
et al.

Abstract: Infusion-related reactions (IRRs) are the major side effects of rituximab administration. Although several studies have reported predictive markers for IRRs in patients with malignancies, there are no such reports for patients without malignancies. Accordingly, we aimed to clarify the predictive markers for rituximabinduced IRRs in renal transplant recipients. This retrospective study included 116 inpatients aged ≥18 years who received an initial dose of 150 mg/m 2 of rituximab for desensitization before renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…In this study, we revealed that the BSA in the IRR group was significantly higher than that in the non-IRR group in adults with frequently relapsing MCNS, consistent with our previous findings [ 7 ]. There is a positive correlation between BSA and blood volume [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, we revealed that the BSA in the IRR group was significantly higher than that in the non-IRR group in adults with frequently relapsing MCNS, consistent with our previous findings [ 7 ]. There is a positive correlation between BSA and blood volume [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we could not perform a multivariate analysis, adjust the p -value to eliminate the possibility of type one error, and calculate a meaningful cutoff for BSA. However, the main outcome of our study was the examination of the relationship between physique-related factors and rituximab-induced IRRs, and our results were consistent with those of previous studies [ 5 , 7 ]. Consequently, we considered that our results were reliable, and the possibility of type one error was low.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations